RECASTING PROJECT MANAGEMENT KNOWLEDGE: A HUMANE TACTIC TO DESIGN THINKING APPROACH - Morgan , Asena; Kyalo , Prof. Dorothy (IJRDO - Journal of Business Management, 2022)
This paper describes the importance of design thinking in project management. Design thinking is critical in guiding managers to deliver elaborate projects. The paper reviews literature on project failure and its reasons, knowledge of project management and illustrate how design thinking can help. Through project formulation, design, implementation, execution and monitoring stages, project managers must think beyond project complexities-they must consider environmental enablers so as to deliver successful projects. Project externalities influence the successful implementation of projects. The need for managers to think critically on their projects design and implementation is discussed later in the paper. The paper concludes by stating that knowledge on project management must be rebuilt through design thinking. This would enhance better project execution and reduce project failures.